The Influence of Attitude, Subjective Norms, and Perceived Behavioral Control on Consumer Purchase Decisions at Starbucks in Jakarta - Siregar, Khairul Azman; Hubbansyah, Aulia Keiko (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effects of Attitude, Subjective Norms, and Perceived Behavioral Control on the Purchase Decisions of Starbucks consumers in Jakarta. This study is motivated by increasing competition in the coffee shop industry and changes in consumer behavior, indicating that purchase decisions are influenced by individual evaluations, social environments, and consumers' perceived ability and ease of making purchases. This study employed a quantitative approach using descriptive and verification methods. Primary data were collected through questionnaires distributed to 100 Starbucks consumers in Jakarta using a purposive sampling technique. Data were analyzed using multiple linear regression with SPSS version 27. The results show that Attitude has a positive and significant effect on Purchase Decisions. Subjective Norms have a positive and significant effect on Purchase Decisions. Perceived Behavioral Control also has a positive and significant effect on Purchase Decisions and is identified as the most dominant variable. The findings indicate that consumers' ability and ease of making purchases are the strongest factors in encouraging the Purchase Decisions of Starbucks consumers in Jakarta. Therefore, business innovation focused on accessibility, digital services, and reducing purchasing barriers may contribute to encouraging consumer Purchase Decisions.